Títeres y la motivación en los niños de las instituciones educativas públicas del nivel inicial del distrito de Andoas 2024 - Guerrero Chino, Teresa (2025)
The main objective of this study was to determine the degree of relationship between the use of titles and motivation in children from Public Educational Institutions of the Initial Level in the District of Andoas in the year 2024. This study is characterized by a quantitative approach . and adopts a non-experimental, correlational and transectional research design. The sample consisted of a total of 241 children from the aforementioned institutions. For data collection, the observation technique was used, using a structured guide as an instrument. The validity of the instrument was ensured through a comprehensive evaluation by a group of experts with extensive experience in the area. The results obtained showed a correlation coefficient of Kendall's Tau-b = 0.741 (p < 0.05), which allowed us to reject the null hypothesis and accept the general hypothesis. Consequently, it is concluded that there is a significant relationship between the use of titles and the level of motivation of children in the Public Educational Institutions of the Initial Level of the District of Andoas in 2024.